Estimation of Spatial Distribution and Fluid Fraction of a Potential Supercritical Geothermal Reservoir by Magnetotelluric Data: A Case Study From Yuzawa Geothermal Field, NE Japan. Issue 2 (14th February 2022) - Ishizu, Keiichi; Ogawa, Yasuo; Nunohara, Keishi; Tsuchiya, Noriyoshi; Ichiki, Masahiro; Hase, Hideaki; Kanda, Wataru; Sakanaka, Shinya; Honkura, Yoshimori; Hino, Yuta; Seki, Kaori; Tseng, Kuo Hsuan; et al.
Abstract: Fluids within the Earth's crust may exist under supercritical conditions (i.e., >374°C and >22.1 MPa for pure water). Supercritical geothermal reservoirs at depths of 2–10 km below the surface in northeastern (NE) Japan mainly consist of magmatic fluids that exsolved from the melt during the course of fractional crystallization. Supercritical geothermal reservoirs have received attention as next‐generation geothermal resources because they can offer significantly more energy than that obtained from conventional geothermal reservoirs found at temperatures <350°C. However, the spatial distribution and fluid fraction of supercritical geothermal reservoirs, which are required for their resource assessment, are poorly understood. Here, the magnetotelluric (MT) method with electrical resistivity imaging is used in the Yuzawa geothermal field, NE Japan, to collect data on the fluid fraction and spatial distribution of a supercritical geothermal reservoir. The collected MT data reveal a potential supercritical geothermal reservoir (>400°C) with dimensions of 3 km (width) × 5 km (length) at a depth of 2.5–6.0 km below the surface. The estimated fluid fraction of the reservoir is 0.1%–4.2% with salinity values of 5–10 wt%. The melt is also imaged below the reservoir, and based on the resistivity model; we develop a mechanism for the evolution of the supercritical geothermal reservoir, wherein upwelling supercritical fluids supplied from the melt are trapped under less permeable silica sealing and accumulate there. Plain Language Summary: As the demand for sustainable energy solutions has increased worldwide, geothermal energy has emerged as a clean and renewable energy source that comes from reservoirs of hot water beneath the Earth's surface. Subsurface fluids in a supercritical state (high temperature and pressure) have received attention as the next‐generation geothermal resources because they can offer significantly more energy than that obtained from conventional geothermal fluids found at temperatures <350°C. Supercritical geothermal fluids are located in various volcanic areas in the world. However, understanding of the spatial distribution and fluid fraction of supercritical fluids, which is necessary for their resource assessment, is limited. Therefore, we use the magnetotelluric (MT) method to obtain information on the spatial distribution and fluid fraction of a supercritical geothermal reservoir in the Yuzawa geothermal field in northeastern Japan. The MT method is sensitive to the subsurface electrical resistivity distribution, which in turn can be used as a proxy for the presence of supercritical fluids. The collected MT data reveal a potential supercritical geothermal reservoir of 3 km (width) × 5 km (length) at a depth of 2.5–6 km below the surface with a fluid fraction of 0.1%–4.2% and salinity of 5–10 wt%. Key Points: A supercritical geothermal reservoir of 3 km (width) × 5 km (length) is imaged using the magnetotelluric method at a depth of 2.5–6.0 km The fluid fraction of the supercritical reservoir is estimated to be 0.1%–4.2% with salinity of 5–10 wt% Upwelling supercritical fluids supplied from the melt are trapped under a less‐permeable silica sealing